Characterization of gamma irradiation-induced mutations in Arabidopsis mutants deficient in non-homologous end joining - Du, Yan (J Radiat Res, 2020)
To investigate the involvement of the non-homologous end joining (NHEJ) pathway in plant mutagenesis by ionizing radiation, we conducted a genome-wide characterization of the mutations induced by gamma rays in NHEJ-deficient Arabidopsis mutants (AtKu70(−/−) and AtLig4(−/−)). Although both mutants were more sensitive to gamma rays than the wild-type control, the AtKu70(−/−) mutant was slightly more sensitive than the AtLig4(−/−) mutant. Single-base substitutions (SBSs) were the predominant mutations in the wild-type control, whereas deletions (≥2 bp) and complex-type mutations [i.e. more than two SBSs or short insertion and deletions (InDels) separated by fewer than 10 bp] were frequently induced in the mutants. Single-base deletions were the most frequent deletions in the wild-type control, whereas the most common deletions in the mutants were 11–30 bp. The apparent microhomology at the rejoined sites of deletions peaked at 2 bp in the wild-type control, but was 3–4 bp in the mutants. This suggests the involvement of alternative end joining and single-strand annealing pathways involving increased microhomology for rejoining DNA ends. Complex-type mutations comprising short InDels were frequently detected in the mutants, but not in the wild-type control. Accordingly, NHEJ is more precise than the backup pathways, and is the main pathway for rejoining the broken DNA ends induced by ionizing radiation in plants.